PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI “BERGERAK BERSAMA” PADA SISWA KELAS V SD - Rhaifaldy Aditya Nugraha; Rosy Aming Rustiyanti; Fine Reffiane; Ristiyani (STKIP Subang, 2026)
Abstract. This study aimed to improve students’ learning outcomes in Bahasa Indonesia through the implementation of the Problem Based Learning (PBL) model on the topic “Bergerak Bersama” in grade V elementary school students. The study employed Classroom Action Research (CAR) conducted in two cycles involving 21 students. Each cycle consisted of planning, implementation, observation, and reflection stages. Data collection techniques included observation, learning outcome tests, and documentation. Data were analyzed descriptively by comparing students’ learning outcomes and learning activities before and after the implementation of the PBL model. The learning process was conducted through problem-solving activities, group discussions, presentations, and contextual learning experiences related to students’ daily lives. The results indicated that the implementation of Problem Based Learning improved students’ learning outcomes and classroom participation. The average score increased from 65 in the pre-cycle to 76 in Cycle I and 88 in Cycle II. Learning mastery improved from 48% in the pre-cycle to 71% in Cycle I and reached 90% in Cycle II. Students also became more active in asking questions, expressing opinions, and collaborating in group discussions. Therefore, the implementation of Problem Based Learning can improve students’ understanding and participation in Bahasa Indonesia learning at elementary school level.